The Correlation Between Students’ Prior Knowledge And Students’ Listening Comprehension Of The Second Grade Students Of MAN 2 Padang Panjang - Nella Fatrisia; Loli Safitri; Syahrul Syahrul; Widya Syafitri (PT. AKSARA AKADEMIA INDONESIA, 2026)
This research was conducted since there were many problems in listening comprehension which were correlated with students’ prior knowledge. There were some problems related to the students’ prior knowledge in comprehending the spoken text. Most of students were difficult to comprehend the spoken text. Some of students are not able to comprehend what the speaker said, although they have prior knowledge about the topic of spoken text. This research aimed to discover the correlation between students’ prior knowledge and listening comprehension. This research was a correlational research. The total of population was 310 students, the sample was 31 students which consisted of 3 or 2 students per class and the researcher used simple random sampling in determining the sample. The data were gotten from test about students’ prior knowledge and listening comprehension that the researcher distributed to students. To analyze the data, product moment Coefficient Correlation ( ρ ) was used to test the Hypothesis, this research used r-hitung formula and consult the result into r-table with α =0,05. From the analysis of the data, it was found that the coefficient of correlation gotten was 0.771 in the range 0.70-0.90 or was in high correlation. It means there was a positive correlation between students’ prior knowledge and their listening comprehension. In other words, the Ha which stated that there is significant correlation between students’ prior knowledge and their listening comprehension was accepted. In conclusion, there was high correlation between students’ prior knowledge and their listening comprehension, if the students had good prior knowledge it will increase their listening comprehension.